Evaluation of Aesthetic, Functional, and Environmental Effects on the Design of Urban Open Spaces: A Case Study of istanbul sishane Park, Turkey - Gökçen Firdevs Yücel Caymaz; Samar Hamameh (Alanya Hamdullah Emin Paşa Üniversitesi, 2020)
Urban spaces reflect the reality of city life, like a mirror. This research aims to examine and analyze the advanced aesthetic, functional, and environmental performance of urban public spaces by assessing the current situation and highlighting the role of creativity in developing these spaces. To clarify the research scope, Şişhane Park in İstanbul, Turkey was studied to define the requirements of creative standards, evaluate these competencies and choose the appropriate architectural style and urban furniture. In addition, to learn ways of preserving those elements for longer life. The analytical descriptive approach was the research method utilized in order to arrive at a set of results that ascertain the reality of the aesthetic, functional, and environmental performance of urban public spaces, and the reflection of the contemporary role in developing these spaces, which can contribute to addressing weaknesses and bolster the strong points in the formation of public urban spaces around the world.